Controlling Hardwoods in Longleaf Pine Restoration - Patrick J. Minogue; Kimberly Bohn; Rick Williams (EDIS)
FOR-125, a 5-page illustrated fact sheet by Patrick J. Minogue, Kimberly Bohn, and Rick Williams, details tools available to manage hardwoods in longleaf stands. Includes references. Published by the UF School of Forest Resources and Conservation, August 2007.